Art & Max - Wiesner, David (Boston : Clarion Books, 2010)
Max wants to be an artist like Arthur, but his first attempt at using a paintbrush sends the two friends on a whirlwind trip through various media, with unexpected consequences.
Keywords: Artists -- Fiction; x; Painting; Lizards